Meningkatkan kemampuan pemecahan masalah matematis siswa SMP: Studi pengembangan media LINEVA dengan model discovery learning - Riska Nur Annisa; Anik Yuliani; Martin Bernard (IKIP Siliwangi, 2026)
Students' mathematical problem-solving ability still needs improvement. This study aimed to develop LINEVA, an interactive learning media assisted by Visual Basic for Applications (VBA) Excel integrated with the Discovery Learning model. This study employed the Research and Development method using the ADDIE model. The participants consisted of 10 students in the limited trial, 20 students in the field trial, and 72 eighth-grade students who were assigned to the experimental and control classes. Data were collected through validation sheets, questionnaires, and mathematical problem-solving tests, then analyzed using descriptive statistics and the Mann–Whitney test. The results indicated that LINEVA achieved a very high level of validity, with scores of 83.64% from material experts and 88.89% from media experts. The media was also categorized as highly practical, obtaining scores of 84.79% in the limited trial and 83.73% in the field trial. The Mann–Whitney test yielded an Asymp. Sig. value of 0.000 (<0.05), indicating that the media effectively improved students' mathematical problem-solving ability. In addition, students' responses were categorized as good, with a percentage of 77.17%. Therefore, LINEVA is considered suitable for use in mathematics learning.